2022
DOI: 10.53550/eec.2022.v28i03.058
|View full text |Cite
|
Sign up to set email alerts
|

Effect of potassium nitrate on germination physiology of magnesium nitrate primed and non-primed rice seeds var. Swarna

Abstract: Present work deals about the influence of graded solution of Potassium Nitrate (KNO3) on germinationphysiology and seedling vigor index, using Magnesium Nitrate [Mg(NO3)2] (4 mM) primed seeds of ricevariety Swarna to ensure the importance of seed priming technology vis -a-vis tolerable capacity of seed /seedling towards KNO3. During experimentation graded solution of KNO3 was taken into petri dishes,containing Mg(NO3)2 primed and non-primed seeds of rice for the study of various parameters, includedgermination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The critical scrutinization of the results for all the abovementioned parameters showed that the application of zinc sulphate heptahydrate and boric acid both have an optimum concentration where the maximum attainments of the values were observed in present case. Similarly, Mondal and Bose (2022) reported that in plant system has the capacity to act as per the concentration of the chemicals, which are beneficial for their growth, otherwise the level more than that may be either toxic or inhibitory. In another study, Farooq et al (2006) noted that the optimum concentration of zinc sulphate heptahydrate and boric acid either used separately or in combined form during the time of seed priming may improve the homeostasis by maintaining the suitable criteria for the germinating seeds and seedling.…”
Section: Resultsmentioning
confidence: 99%
“…The critical scrutinization of the results for all the abovementioned parameters showed that the application of zinc sulphate heptahydrate and boric acid both have an optimum concentration where the maximum attainments of the values were observed in present case. Similarly, Mondal and Bose (2022) reported that in plant system has the capacity to act as per the concentration of the chemicals, which are beneficial for their growth, otherwise the level more than that may be either toxic or inhibitory. In another study, Farooq et al (2006) noted that the optimum concentration of zinc sulphate heptahydrate and boric acid either used separately or in combined form during the time of seed priming may improve the homeostasis by maintaining the suitable criteria for the germinating seeds and seedling.…”
Section: Resultsmentioning
confidence: 99%